Three-dimensional electro-responsive carbonreinforced hydrogels for neural tissue engineering - Fernandes, Cristiana Barbosa Lopes (2022)
The main objective of the present work consists of the optimization of the production of three-dimensional electro-responsive carbon-reinforced hydrogels, to study their cytocompatibility with neural stem cells (NSCs) for neural tissue engineering. For that matter, initially vertically aligned carbon nanotubes (VA-CNTs) with two different patterns were prepared by thermal chemical vapor deposition (T-CVD): (1) VA-CNTs dense forest and (1) VA-CNTs micropillars. Furthermore, the substrates previously described were studied after acetone vapor treatment, resulting in a cellular and “flower-like” pattern morphology, respectively. Structural characterization of the respective samples was made using scanning electron microscopy (SEM), transmission electron microscopy (TEM) and the measurement of the water contact angle (WCA). The integration with gelatinmethacryloyl (GelMA) -based hydrogels were explored in the different studied samples. The influence of the different VA-CNTs prepared patterns was studied by the evaluation of the cell behavior with resort to NSCs. By immunocytochemical staining, cell viability assays and SEM, it was observed the cells affinity for the diverse carbon structures, in comparison to the silicon (Si) substrate. Besides, it was also verified the suitability of the VA-CNTs platforms for cell viability and proliferation. The collapsed VA-CNTs substrate made evident the tendency for cell differentiation into neurons, possibly due to their superficial roughness at the nanoscale, which favors this biological mechanism. The results obtained demonstrated that VA-CNTs based structures favors the proliferation and differentiation of NSCs, making them promising as future threedimensional electroresponsive structures with excellent performances for neural tissue engineering.